PROSES PEMISAHAN AGUNAN DAN BRIMEN SEBAGAI UPAYAPENINGKATAN AKURASI DATA KREDIT DI BANK BRI UNIT BANGKO KOTA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The management of credit data in banking institutions requires high accuracy and precision to ensure smooth services and minimize administrative errors. One of the efforts carried out by Bank Unit Bangko Kota is the separation of collateral (agunan) and BRIMEN (BRI Management System) as part of a strategy to improve the quality of credit data. This study aims to analyze the process of collateral and BRIMEN separation, as well as its contribution to enhancing credit data accuracy. The research method used is descriptive qualitative with a case study approach, through direct observation, interviews with related employees, and documentation. The results indicate that the separation of collateral and BRIMEN provides positive impacts in facilitating identification, recording, and storage of credit files. In addition, this step reduces the potential for data duplication, accelerates the verification process, and increases customer trust in the quality of banking services. Therefore, the implementation of collateral and BRIMEN separation at Bank Unit Bangko Kota is proven to be an effective strategy in supporting the improvement of credit data accuracy and operational efficiency.